Adalimumab for Corticosteroid and Infliximab-Resistant Immune Reconstitution Inflammatory Syndrome in the Setting of TB/HIV Coinfection. (30th January 2018) - Lwin, Nilar; Boyle, Michael; Davis, Joshua S
Abstract: Corticosteroids are the mainstay of therapy for immune reconstitution inflammatory syndrome (IRIS). However, little is known about how to treat IRIS unresponsive to steroids. We report a patient with HIV-TB coinfection who was unresponsive to first prednisolone and then infliximab but whose IRIS resolved with adalimumab.